(untitled) (Academic Journal of Internal Affairs, 2024)
Aim: The aim of the study is to investigate the background and psychology of a problem that often occurs in the application of law and is therefore of outstanding theoretical and practical importance – the wrong verdict due to the false memory of witnesses – in order to avoid the biggest judicial failures (justizmord). Methodology: The study was prepared by analysing international and Hungarian psychological theses and studies, describing relevant legal cases, and processing the international and domestic literature. Findings: The complexity, fragility and influence of human memory must be kept in mind during the procedure of the participants of the justice system, as well as the interrogation techniques to promote adequate memory, so that false decisions cannot be made in the justice system. Value: The credibility and accuracy of testimonies can be the key to finding out the material truth in the justice system, therefore the experiments described in the study and the techniques that support the testified testimony provide assistance to law enforcement.